Reducing Costs Thru The Implementation Of The Green Value Chain and Green Kaizen - Zina Hamza Ghali (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
The research aims to demonstrate the role of the green value chain and green Kaizen in reducing costs and improving operational and environmental efficiency in industrial economic units, thru their application in the General Company for Electrical Industries on the electric heater product. The research adopted the descriptive-analytical method based on field study and analysis of the actual cost data of the product, aiming to diagnose areas of waste and the possibility of cost reduction thru the adoption of green practices and continuous improvement. The research addressed the concept of the green value chain as a framework that integrates environmental considerations into all production activities, starting from research and development, design, and manufacturing, to marketing and recycling. It also discussed the concept of green Kaizen, which focuses on continuous improvement and reducing waste in time, materials, energy, and production defects. The PDCA cycle was also applied to diagnose and address production problems and improve the efficiency of operational processes. The research concluded that the application of the green value chain contributed to achieving financial savings by restructuring some activities, replacing traditional materials with more cost-effective and efficient eco-friendly alternatives, as well as enhancing recycling activities.